physics

posted by .

Prove that sinx~x for small vibration

  • physics -

    sin(x) = x - x^3/3! + x^5/5! - . . .

    for small x, the higher powers get vanishingly tiny, and we are left with

    sin(x) ~ x

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Trig........

    I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top and …
  2. Pre-calc

    prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i need steps to show how i got the answer generally, it is a good idea to change all trig ratios to sines and cosines, and start with the more complicated-looking side. …
  3. Mathematics - Trigonometric Identities

    Prove: sinx + tanx = tanx (1 + cosx) What I have so far: LS: = sinx + tanx = sinx + (sinx / cosx) = (sinx) (cosx) + sinx / cos = tanx (cosx + sinx) I don't know what to do now
  4. Mathematics - Trigonometric Identities

    Prove: sin^2x - sin^4x = cos^2x - cos^4x What I have, LS = (sinx - sin^2x) (sinx + sin^2x) = (sinx - 1 -cos^2x) (sinx + 1 - cos^2x) = sin^2x + sinx - sinx - cos^2xsinx - cos^2xsinx - 1 - 1 + cos^4x = sin^2x - 2cos^2xsinx - 2 + cos^4x …
  5. Mathematics - Trigonometric Identities

    Prove: (tanx)(sinx) / (tanx) + (sinx) = (tanx) - (sinx) / (tanx)(sinx) What I have so far: L.S. = (sinx / cosx) sinx / (sinx / cosx) + sinx = (sin^2x / cosx) / (sinx + (sinx) (cosx) / cosx) = (sin^2x / cosx) / (cosx / sinx + sinxcosx)
  6. Math - Pre- Clac

    Prove that each of these equations is an identity. A) (1 + sinx + cos x)/(1 + sinx + cosx)=(1 + cosx)/sinx B) (1 + sinx + cosx)/(1 - sinx + cosx)= (1 + sin x)/cosx Please and thankyou!
  7. math

    1. Prove the identity:cosx/1-tanx+sinx/1-cotx=sinx+cosx 2.Prove the identity: cosx/1+sinx+1+sinx/cosx=2secx
  8. Trig Help

    Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)] =[sinx+sin^2x]/[sinx+1] =[sinx+(1-cos^2x)]/[sinx+1] =?
  9. Maths

    If y=Sinx^Sinx^Sinx.......infinity then prove that dy/dx=2ycotx/1-ylog(sinx).?
  10. Precalculus/Trig

    Prove the following identity: 1/tanx + tanx = 1/sinxcosx I can't seem to prove it. This is my work, I must've made a mistake somewhere: Converted 1/tanx: 1/sinx/cosx + sinx/cosx = 1/sinxcosx Simplified 1/sinx/cosx: cosx/sinx + sinx/cosx …

More Similar Questions